2022
DOI: 10.5219/1710
|View full text |Cite
|
Sign up to set email alerts
|

Bromine in chicken eggs, feed, and water from different regions of Ukraine

Abstract: The purpose of these studies was to analyse and compare the content of bromine in samples of chicken eggs, feed, and water from different regions of Ukraine in the dynamics of 2016 – 2020: with an increased risk of bromine in products (Kharkiv, Poltava, Dnipropetrovsk and Mykolaiv regions) and outside the risk zone (Volyn, Vinnytsia and Zaporizhzhia). Studies of bromine content in eggs, feed, and water were performed in the laboratory of toxicological monitoring of the National Scientific Center "Institute of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Similar results were obtained for the feeding of triazoline compounds to broiler chickens in the experiments of O. Orobchenko et al (2022), where a positive effect on reducing the time of poultry fattening was found, which is important for industrial meat poultry production. The developmental dynamics of broiler turkeys, which were used in the experiment to study the effect of triazoline compounds on meat productivity, showed that the introduction of GKPF-109 caused a large difference between the weight of different parts of the carcasses.…”
Section: Indicatorssupporting
confidence: 82%
“…Similar results were obtained for the feeding of triazoline compounds to broiler chickens in the experiments of O. Orobchenko et al (2022), where a positive effect on reducing the time of poultry fattening was found, which is important for industrial meat poultry production. The developmental dynamics of broiler turkeys, which were used in the experiment to study the effect of triazoline compounds on meat productivity, showed that the introduction of GKPF-109 caused a large difference between the weight of different parts of the carcasses.…”
Section: Indicatorssupporting
confidence: 82%
“…The quality of eggs used for incubation is the most crucial and essential factor in accurately forecasting the hatchability and viability of offspring and acquiring safe and excellent poultry products (Goliomytis et al, 2015;Melo et al, 2021). It should be noted that the quality of hatching eggs is influenced by an array of biotic and abiotic factors (Nasri et al, 2020;Orobchenko et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining quality livestock products is not possible without scientifically sound, complete feeding of productive animals. The quality and safety of the feed used, and the level of their contamination by abiotic and biotic factors are important (Gosling et al, 2021;Orobchenko et al, 2022).…”
Section: Introductionmentioning
confidence: 99%